EBIC investigations on polar and semipolar InGaN LED structures. Issue 1 (20th August 2015) - Knab, Manuel; Hocker, Matthias; Felser, Timo; Tischer, Ingo; Wang, Junjun; Scholz, Ferdinand; Thonke, Klaus
Abstract: Polar and semipolar LED structures with InGaN quantum wells (QWs) were investigated in a scanning electron microscope (SEM) using simultaneously electron beam induced current (EBIC) and cathodoluminescence (CL). EBIC yields important information about depletion region, leakages, and the overall functionality of the pn‐junction and allows to determine the diffusion length of the generated minority carriers on both sides of the pn‐junction. Spectrally and spatially resolved CL measurements yield both, information about the QW quality and about centers of non‐radiative recombination. EBIC measurements were carried out in top‐view and in cross‐section between 26 K and room temperature. The diffusion lengths measured for polar and semipolar structures prove the better crystal quality of the polar structures in terms of the higher carrier diffusion length and its increase for lower temperatures, as expected. On the semipolar structures, top‐view EBIC measurements detect specific areas, where the pn‐junction seems to be disturbed. The comparison of EBIC and CL measurements shows interesting correlations of the EBIC signal and the emission wavelengths of the quantum wells.